Prevalence of and factors associated with long COVID among diverse healthcare workers in the UK: a cross-sectional analysis of a nationwide study (UK-REACH) - Kamlesh Khunti; Katherine Woolf; Luke Bryant; Manish Pareek; Carolyn Tarrant; Christopher A Martin; Amani Al-Oraibi; Laura B Nellums (BMJ Open)
Objectives To assess the prevalence of UK healthcare workers (HCWs) who reported symptoms of COVID-19 lasting for longer than 5 weeks and examine associated factors with experiencing long COVID in an ethnically diverse cohort.Design A cross-sectional study using data from the UK Research study into Ethnicity And COVID-19 Outcomes in HCWs cohort study.Setting Data were collected electronically between December 2020 and March 2021.Participants Individuals aged 16 years or older, residing in the UK, and working as HCWs or ancillary workers in a healthcare setting and/or registered with one of the seven major UK healthcare professional regulators.Primary and secondary outcome measures The main outcome was long COVID (symptoms>5 weeks). The primary exposure of interest was self-reported ethnicity. We employed univariable and multivariable logistic regression to identify associations. We adjusted for demographic information, health status and existing long-term conditions in our multivariate analysis.Results In our analysis of 11 513 HCWs, we found that 2331 (20.25%) reported COVID-19, of whom 525 (22.52%) experienced long COVID. There were no significant differences in risk of long COVID by ethnic group. In terms of other demographic characteristics, the majority of those experiencing long COVID were female (80.0%) and were slightly older than those who did not experience long COVID (median age 46 (IQR 36–54)). In multivariable analyses of those who reported having had COVID-19, HCWs in nursing/midwifery roles (adjusted OR (aOR) 1.76, 95% CI 1.26 to 2.46; p=0.001) and allied health professions (aOR 1.42, 95% CI 1.05 to 1.93; p=0.023) had higher odds of experiencing long COVID compared with those in medical roles. Other factors significantly associated with long COVID included self-reported psychological conditions (eg, depression and anxiety) and respiratory conditions (eg, asthma).Conclusions In this large ethnically diverse cohort study, more than one in five UK HCWs reported experiencing long COVID after acute COVID-19 during the first year of the pandemic. We found that specific demographic (older age and female gender) and occupational factors (nursing/midwifery and allied health professions) were associated with higher odds of long COVID. Notably, there were no significant differences in the risk of long COVID by ethnic group. Further research and collaborative efforts are urgently needed to address these factors effectively, develop targeted interventions and understand the temporal and longitudinal dynamics of the condition.